Penerapan Standar Akuntansi Keuangan Entitas Mikro, Kecil, dan Menengah (SAK EMKM) dalam Persekutuan: Studi Kasus pada Cipadas Coffee and Chill - Fadly Ardiansyah; May Inggri Sihombing; Siti Rodiah (International Forum of Researchers and Lecturers, 2025)
This research focuses on the phenomenon that occurs at Cipadas Coffee and Chill, a business in Sukajadi District, Pekanbaru City, which has been operating for about three years but has not prepared financial reports based on Micro, Small and Medium Entity Financial Accounting Standards (SAK EMKM). This research aims to identify and analyze the obstacles faced by partnership owners in preparing financial statements based on SAK EMKM. In this study, researchers used a qualitative approach with the case study method. The data used is primary data obtained from direct interviews with business owners. The results showed that Cipadas Coffee and Chill had not implemented SAK EMKM in compiling its financial reports due to several reasons, namely the owner's lack of knowledge about SAK EMKM and the procedures for preparing appropriate financial reports, lack of owner participation in socialization activities about SAK EMKM and owner orientation which was more inclined to the aspect of operating profit. Thus, the results of this study indicate the need for further education and socialization efforts to partnership owners regarding the importance of applying SAK EMKM in preparing financial reports. With adequate knowledge and understanding, it is hoped that Cipadas Coffee and Chill will be able to prepare financial reports in accordance with applicable accounting standards, thereby increasing transparency and financial accountability.